Enhancing Student Participation through a Validated Cooperative Flipped Classroom Framework in Technology Education - Jusmita Weriza; Irfan Ananda Ismail; Henny Yustisia; Zulkifli; Lise Asnur (Jurnal Penelitian Pendidikan IPA, 2025)
Abstract: This study addresses the challenges of limited student participation and ineffective group learning in Information Systems Analysis & Design education. The objective was to develop, validate, and test a seven-syntax flipped classroom model integrated with cooperative learning. The study employed Borg and Gall's R&D methodology with 60 students in experimental and control groups at Universitas Ekasakti. Data were analyzed using descriptive statistics for validity and practicality, and independent t-tests for effectiveness. The results demonstrated exceptional model validity (≥88%), high practicality from instructors (≥85%) and students (≥86%), and significant effectiveness. The experimental group showed superior cognitive (85.2 vs. 75.1), affective (collaboration and responsibility), and psychomotor outcomes (88.5 vs. 78.2) compared to the control group. In conclusion, the validated seven-syntax model successfully improves student participation and learning outcomes by balancing asynchronous learning with synchronous collaboration, providing a valuable framework for technology education.